Être le dernier : Ishi, l’homme-archive - Carine Trevisan (Amnis)
Ishi, sole survivor of the Yana Indian tribe, which was exterminated after a policy of predation and a brutal colonization of his land, the last man to speak the language of this tribe and to know all the technical skills dating back to Stone age (tool making, hunting…), gets into the white “civilization” in 1911. He lived on the Parnassus campus, where the University of California Museum of Anthropology was located. He made efforts to transmit all his knowledge and skills as well as the annihilated culture of his tribe. This paper explores the ways in which in his book Ishi, the Last Wild Indian of North America Testifies, Theodora Kroeber shows how, in an almost total lack of any documentary sources, a man is turned into an archive.